Evaluating transience of a potential geothermal flux anomaly beneath a tributary ice stream of Thwaites Glacier, West Antarctica - DeSanto, John B. (2013)
The Amundsen Sea Embayment of the West Antarctic ice sheet (WAIS) is currently one of the most rapidly changing sectors of a continental ice sheet. As a marine ice sheet, the WAIS is in a potentially unstable configuration. A model is proposed to evaluate the effect of geothermal flux on flow in ice streams using ice layer drawdown anomalies, features identifiable by a thick layer package resting on top of deformed ice. Drawdown anomalies represent either significant loss or mechanical deformation of basal ice. Several features with the geometry of drawdown anomalies are identified in Thwaites Glacier along an ice stream tributary near Mt. Takahe. These anomalies correlate with the surface ice velocity and have thick layer packages that age at a constant rate, implying deformation at a single origin corresponding to an upstream edifice. The abnormal amplitude of upstream drawdown anomalies implies a thermal event at the same edifice 1000-2000 years ago. This provides another example of high heterogeneous geothermal flux in the WAIS. Physics Institute for Geophysics